2010
DOI: 10.1111/j.1365-2958.2010.07330.x
|View full text |Cite
|
Sign up to set email alerts
|

Substrate path in the AcrB multidrug efflux pump of Escherichia coli

Abstract: SummaryA major tripartite multidrug efflux pump of Escherichia coli, AcrAB-TolC, confers resistance to a wide variety of compounds. The drug molecule is captured by AcrB probably from the periplasm or the periplasm/inner membrane interface, and is passed through AcrB and then TolC to the medium. Currently, there exist numerous crystallographic and mutation data concerning the regions of AcrB and its homologues that may interact with substrates. Starting with these data, we devised fluorescence assays in whole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
113
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(121 citation statements)
references
References 40 publications
(74 reference statements)
6
113
1
1
Order By: Relevance
“…1), which collapses in the extrusion protomer, plays a major role in the binding and selection of substrates by AcrB. Indeed site-directed mutagenesis and real-time efflux experiments confirmed this hypothesis (17)(18)(19)(20)(21), although very recently some antibiotics have been cocrystallized bound to a more proximal binding pocket in the access protomer (22,23), which presumably represents an earlier stage in the drug efflux process, and it is consistent with earlier cocrystallization and biochemical studies (24,25).…”
supporting
confidence: 79%
“…1), which collapses in the extrusion protomer, plays a major role in the binding and selection of substrates by AcrB. Indeed site-directed mutagenesis and real-time efflux experiments confirmed this hypothesis (17)(18)(19)(20)(21), although very recently some antibiotics have been cocrystallized bound to a more proximal binding pocket in the access protomer (22,23), which presumably represents an earlier stage in the drug efflux process, and it is consistent with earlier cocrystallization and biochemical studies (24,25).…”
supporting
confidence: 79%
“…The neighboring residues T98C (from the previous study [3]), E95C, D99C, and A100C were negative. Again, as expected from the wide dimension of this on May 9, 2018 by guest http://jb.asm.org/ large cavity, the efflux blocking assay with pyrene maleimide gave negative results with G97C.…”
mentioning
confidence: 63%
“…Each of these residues was changed into Cys by using the QuikChange (Stratagene) approach in the plasmid pSPORT1-CLBH, expressing cysteine-less AcrB with a hexahistidine tag at its C terminus (13). RAM-1334 (MC4100 ⌬ara ⌬acrB) was the host strain, and the whole cells were treated with 6 M Bodipy FL maleimide (Invitrogen) for 1 h at room temperature exactly as described earlier (3). (That Bodipy FL maleimide is an AcrB substrate was confirmed by the observation that the labeling of endogenous proteins under similar conditions increased significantly in RAM1334, in comparison with its isogenic acrB ϩ parent RAM1336 [Hong-Suk Kim, personal communication]).…”
mentioning
confidence: 99%
“…Recent studies on the crystal structure of substrate bound AcrB (28)(29)(30) and biochemical mapping of the substrate path (31,32) have shown that there are multiple drug-binding sites in the large periplasmic domain of AcrB. We propose that AcrZ binding to AcrB could trigger conformational changes in the periplasmic domain, thus directly affecting the recognition and capture of certain substrates, such as substrates with lower hydrophobicity (Fig.…”
Section: Discussionmentioning
confidence: 94%